Microwave activation of electrochemical processes: enhanced PbO2 electrodeposition, stripping and electrocatalysis - Marken, F; Tsai, Y; Saterlay, A; Coles, B; Tibbetts, D; Holt, K; Goeting, C; Foord, J; Compton, R (2001)
Microwave activation of electrochemical processes has recently been introduced as a new technique for the enhancement and control of processes at electrode|solution (electrolyte) interfaces. This methodology is extended to processes at glassy carbon and boron-doped diamond electrodes. Deposition of both Pb metal and PbO2 from an aqueous solution of Pb2+ (0.1 M HNO3) are affected by microwave radiation. The formation of PbO2 on anodically pre-treated boron-doped diamond is demonstrated to change from kinetically sluggish and poorly defined at room temperature to nearly diffusion controlled and well defined in the presence of microwave activation. Calibration of the temperature at the electrode|solution (electrolyte) interface with the Fe3+/2+ (0.1 M HNO3) redox system allows the experimentally observed effects to be identified as predominantly thermal in nature and therefore consistent with a localized heating effect at the electrode|solution interface. The microwave-activated deposition of PbO2 on boron-doped diamond remains facile in the presence of excess oxidizable organic compounds such as ethylene glycol. An increase of the current for the electrocatalytic oxidation of ethylene glycol at PbO2/ boron-doped diamond electrodes in the presence of microwave radiation is observed. Preliminary results suggest that the electrodissolution of solid microparticles of PbO2 abrasively attached to the surface of a glassy carbon electrode is also enhanced in the presence of microwave radiation.